Health risks from heavy metals in cosmetic products available in the online consumer market - Alicja Kicińska; Magdalena Kowalczyk (Scientific Reports)
Abstract The skin is a very sensitive organ that covers and protects the entire body. It is one of the routes by which chemicals present in e.g., personal care products are absorbed into the body. The quality of cosmetic products and their safety for consumers depend on their chemical composition. Cosmetics are produced from various ingredients, including dyes that contain e.g., Cr6+ and Ni at concentrations that can be hazardous to human health. Entities that introduce cosmetic products in the market are responsible for their safety and for ensuring that their chemical composition complies with relevant standards. However, the online market offers products of different brands manufactured in plants located in countries that have less restrictive regulations than those in place in the EU or the US. In the present study, we carried out analyses (mineralization with aqua regia HCl: HNO3) to determine the concentrations of selected metals (Cr, Fe, Ni, Mn and Zn) using ICP-MS in 23 samples of cosmetics (foundations, blushes, lipsticks, creams, face masks and eye shadows) in order to calculate the health risks associated with their daily use. We calculated the margin of safety (MoS), hazard index (HI) and the hazard quotient (HQ) and carried out a quantitative risk assessment (QRA) to answer the question of whether cosmetics available in the online market are safe for consumers when used in daily care routines. The results showed wide ranges of heavy metal concentrations in the cosmetics analyzed. The mean concentrations of the elements decreased in the following order (in mg/kg): Fe (6407) > Zn (190) > Mn (88) > Cr (24) > Ni (8). The MoS, HQ and HI values calculated for all the samples of cosmetics indicated that the products do not present a risk to human health.